2021
DOI: 10.1038/s41524-021-00550-4
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening study of double transition metal carbonitrides M′2M″CNO2-MXene as catalysts for hydrogen evolution reaction

Abstract: Two-dimensional (2D) transition metal carbonitrides (MXene) have attracted growing interest in electrocatalytic hydrogen production due to its structural and electronic properties. In this work, the hydrogen evolution reaction (HER) activity of all 64 O-terminated ordered double transition metal carbonitrides in the form of M′2M″CNO2 (M′ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; M″ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta) has been investigated by well-defined density functional theory (DFT) calculations. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…In addition to experimental means, Li's group studied the HER activities of 64 O-terminated ordered double transition metal carbonitrides (M′ 2 M″CNO 2 , M′ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; M″ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta) utilizing DFT calculation (Fig. 4c) [94]. The results showed that Ti 2 NbCNO 2 had a small hydrogen adsorption Gibbs free energy (ΔG H* , 0.02 eV), abundant C-side catalytic centers, and great stability; therefore, it is expected to be a Pt-like HER catalyst (Fig.…”
Section: Carbonitridementioning
confidence: 99%
“…In addition to experimental means, Li's group studied the HER activities of 64 O-terminated ordered double transition metal carbonitrides (M′ 2 M″CNO 2 , M′ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; M″ = Ti, V, Cr, Zr, Nb, Mo, Hf, Ta) utilizing DFT calculation (Fig. 4c) [94]. The results showed that Ti 2 NbCNO 2 had a small hydrogen adsorption Gibbs free energy (ΔG H* , 0.02 eV), abundant C-side catalytic centers, and great stability; therefore, it is expected to be a Pt-like HER catalyst (Fig.…”
Section: Carbonitridementioning
confidence: 99%
“…[58] The design of MXenes with interlayer spacing, hole, doping, functional groups, different chemical components, as well as the loaded, sandwiched, encapsulated, 3D printing construction strategies, have been attractive and proposed. [59][60][61][62][63] Moreover, the design of MXenes profoundly influences on the hydrogenevolution reactions, [38,62] indicating the great potential of MXenes for structure design, as well as the MXenes-based composites. [64,65] All these character structures and prop-erties of MXenes supply diversified choices for designing MXenes-based composites as the candidate for packaging materials to accomplish the preservation, containment, antimicrobial and communication functions (Figure 1).…”
Section: The Typical Structure and Propertiesmentioning
confidence: 99%
“…1 nm thick. [ 54–91 ] Controlling spacing between the 2D sheets has been significantly developed for the gases separation, water purification, and dialysis. [ 92 ] The application of nanoclays in packaging membranes derives from the advantages of low cost, facile preparation, high stability, aboudent resources, and effectiveness.…”
Section: The Structure Of Mxenesmentioning
confidence: 99%
“…The ordered double transition metals carbides M’M”C have been recently found as a new member of the MXenes family. The combination of both metals and mixed carbon-nitrides might potentially expand the range of accessible properties and applications greatly [ 21 ]. Recently, a new layered MXene VCrC with excellent metallic properties with near-zero energy band gap has aroused the interests of researchers.…”
Section: Introductionmentioning
confidence: 99%